Blended learning in mathematic: the fusion of GeoGebra and Edmodo for enhanced problem-solving abilities - Nasrullah, Anton; Aminah, Mimih; Umalihayati, Umalihayati; Rahmadani, Kurniati; Widodo, Sri Adi; Husni, Mohamad (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research investigates the effectiveness of problem-based mathematics learning through blended learning with the help of Edmodo and GeoGebra in improving problem-solving skills in mathematics learning. The primary motivation of this research is to develop a learning approach that can overcome challenges in solving mathematical problems. The method used in this study used a quantitative approach, and a quasi-experimental pre-test and post-test control group design was applied. This study involved 72 students in two semesters from a university in Banten, Indonesia, with 36 students in the experimental class (11 male and 25 female) and 36 in the control class (10 male and 26 female). Data was collected through problem-solving tests before and after the learning intervention—data analysis using paired t-tests and independent t-tests. The group using Edmodo-GeoGebra (BL-UEG) and the group Edmodo without GeoGebra (BL-EWG) experienced an increase in the moderate category. In conclusion, problem-based mathematics learning through blended learning with the help of Edmodo and GeoGebra can be an effective alternative learning model for improving students’ problem-solving abilities in mathematics. Therefore, this approach deserves further exploration in learning settings.